UMP Press publishes 6 new books - Ameerah Humaira', Mohamad Hilmi; Nur Hartini, Mohd Hatta (UMPSA, 2022)
PEKAN, 13 January 2022 – Universiti Malaysia Pahang (UMP) Press started the new year this time by organising a mini-launch of six of its latest published books at the 6th SUARA UMP Aspirations Ceremony, which was completed by the Dean of the Faculty of Mechanical and Automotive Engineering Technology (FTKMA), Professor Dr. Mahadzir Ishak, at the Executive Lounge, UMP Pekan Library.